2017
DOI: 10.3389/fphar.2017.00183
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Biochemical Endothelial Profiling In Vivo in a Murine Model of Endothelial Dysfunction; Comparison of Effects of 1-Methylnicotinamide and Angiotensin-converting Enzyme Inhibitor

Abstract: Although it is known that 1-methylnicotinamide (MNA) displays vasoprotective activity in mice, as yet the effect of MNA on endothelial function has not been demonstrated in vivo. Here, using magnetic resonance imaging (MRI) we profile the effects of MNA on endothelial phenotype in mice with atherosclerosis (ApoE/LDLR-/-) in vivo, in comparison to angiotensin (Ang) -converting enzyme (ACE) inhibitor (perindopril), with known vasoprotective activity. On a biochemical level, we analyzed whether MNA- or perindopri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Interestingly, several papers reported that MNA—a terminal metabolite of nicotinamide clearance—at pharmacological doses, can improve endothelial function in humans and in experimental animals [ 13 , 56 , 57 ]. Domagala et al [ 56 ] demonstrated that MNA ameliorated endothelial dysfunction measured as flow-mediated vasodilation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several papers reported that MNA—a terminal metabolite of nicotinamide clearance—at pharmacological doses, can improve endothelial function in humans and in experimental animals [ 13 , 56 , 57 ]. Domagala et al [ 56 ] demonstrated that MNA ameliorated endothelial dysfunction measured as flow-mediated vasodilation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…At the stage of advanced metastasis associated with robust systemic inflammation, the NO-dependent response in aorta was impaired, while the endothelium-independent response was preserved. Interestingly, downregulation of a NO-dependent endothelial activity was associated with a compensatory increase in COX-2-mediated synthesis of PGI 2 , a vasoprotective molecule with known anti-metastatic potential [ 11 , 12 , 18 20 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both ACEI and ARB have exact antihypertensive effects, as well as clinical effects such as protecting the cardiovascular and cerebrovascular, improving renal function, reducing left ventricular hypertrophy, preventing heart failure and preventing atrial fibrillation. Existing studies suggest that ACEIs, such as captopril or Lisinopril, do not affect the activity of ACE2, 10 and there is no evidence that ACEI or ARB may bring special effects to patients with COVID-19 infection or new coronary pneumonia damage. So, we recommend that the overall control of patients with new coronary pneumonia is persistent, and most of them do not need to adjust hypertension drugs.…”
Section: Discussionmentioning
confidence: 99%